Prajātantrada heddāri, athavā, Ṭenasi Kandarada yōjane : Ṭīvīē - Bhaṭṭa, Ku. Śi. Haridāsa (Kuñjibeṭṭu Śiva Haridāsa), 1923- (SAMP early 20th-century Indian books project ;, 1950)
On Tennessee Valley Authority.